Phytochemical screening and antibacterial activity of kaduk (piper sarmentosum) / Ropisah Me … [et al.] - Me, Ropisah; Ayob, Nurul Liyana; Amran, Intan Munirah; Sahariman, Norhidayah (Universiti Teknologi MARA Cawangan Pahang, 2020)
Piperaceae species especially Kaduk (Piper Sarmentosum) is one of the most valuable herbs. Therefore, this study was focused on examining aimed the extraction of kaduk leaves, to determine the compounds in the extracted sample and investigate their antibacterial features. The grinded kaduk leaves (Piper sarmentosum) were extracted by using two different solvent namely chloroform and ethanol by using hot extraction method. The percentage yield obtained for ethanol extract was 10.5%, higher as compared to the percentage yield of chloroform extract, which was 8.92%. The ethanol extract has indicated the presence of most phytochemicals such as flavonoid, tannin, terpenoid, alkaloid and phenolic compounds. Meanwhile, chloroform extract showed only the presence of saponin compounds. Each of the crudes was also investigated for their biological activities towards four different bacteria by using the disc diffusion method. The result reveals that ethanol extract of kaduk leaves have potential for being antibacterial against gram positive bacteria.